2020
DOI: 10.1021/acs.analchem.9b01974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Combined Precursor Isotopic Labeling and Isobaric Tagging Performance on Orbitraps To Study the Peripheral Proteome of Alzheimer’s Disease

Abstract: Combined precursor isotopic labeling and isobaric tagging (cPILOT) is an enhanced multiplexing strategy currently capable of analyzing up to 24 samples simultaneously. This capability is especially helpful when studying multiple tissues and biological replicates in models of disease, such as Alzheimer’s disease (AD). Here, cPILOT was used to study proteomes from heart, liver, and brain tissues in a late-stage amyloid precursor protein/presenilin-1 (APP/PS-1) human transgenic double-knock-in mouse model of AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Experiments are on-going in our laboratory to further evaluate comparisons of the manual and automated cPILOT workflows. Based on previous reports from our laboratory, the CV%'s of protein reporter ion intensities in the manual cPILOT were on average 20% with some outliers exceeding this value 12 .…”
Section: Representative Resultsmentioning
confidence: 75%
“…Experiments are on-going in our laboratory to further evaluate comparisons of the manual and automated cPILOT workflows. Based on previous reports from our laboratory, the CV%'s of protein reporter ion intensities in the manual cPILOT were on average 20% with some outliers exceeding this value 12 .…”
Section: Representative Resultsmentioning
confidence: 75%
“…The collection of multiple fragment ions increases the intensities of reporter ions, thus increasing the probability of having quantitative information in all channels. As seen in the recent work of King and Robinson, using SPS-MS 3 , in addition to the targeted mass difference strategy, increased both the percentage of light and heavy dimethylation pair detections and peptide quantifications . Previous analyses have shown that using Lys-C results in longer peptides, thus reducing ionization and detection.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in the recent work of King and Robinson, using SPS-MS 3 , in addition to the targeted mass difference strategy, increased both the percentage of light and heavy dimethylation pair detections and peptide quantifications. 37 Previous analyses 21 have shown that using Lys-C results in longer peptides, thus reducing ionization and detection. Hence, trypsin was employed, resulting in ∼80% of K-terminated peptides (Supplemental Table S2) available for TMT labeling and subsequent detection.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Currently, we used a 50× carrier to obtain good proteome coverage in the RTS-based protein identification and quantification; however, we suggest that the carrier-sample ratio should be further reduced to 10× or lower with the sensitivity improvement of the RTS algorithm. The reduced proteome coverage due to low carrier ratio could be improved using isobaric match between runs (iMBR) algorithm, as demonstrated by recent studies. , In addition to sensitivity and quantification accuracy, other technical improvements such as analysis throughput could be achieved by using higher multiplex isobaric reagents or combined precursor isotopic labeling and isobaric tagging (cPILOT) approaches. , Moreover, because of the inherent differences in ion detection between LIT and OT, it could be highly valuable to perform an additional study on the response linearity and quantification dynamic ranges of both detection methods for single-cell-scale samples. Such study could provide insight on their performance in the absolute quantification of proteins.…”
Section: Discussionmentioning
confidence: 99%